2020
DOI: 10.1200/jco.2020.38.15_suppl.6007
|View full text |Cite
|
Sign up to set email alerts
|

Sequential chemoradiation versus radiation alone or concurrent chemoradiation in adjuvant treatment after radical hysterectomy for stage IB1-IIA2 cervical cancer (STARS Study): A randomized, controlled, open-label, phase III trial.

Abstract: 6007 Background: There are limited data from previous studies regarding whether the addition of chemotherapy to adjuvant radiation after radical surgery improves outcomes among patients with early-stage cervical cancer and adverse pathological factors. Methods: This was a prospective randomized trial including patients with FIGO 2009 stage IB1-IIA2 cervical cancer and squamous-cell, adenocarcinoma, or adenosquamous carcinoma with at least one adverse factor after radical hysterectomy. Patients were randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Treatment discontinuation rates were high in the chemotherapy arms, 5 with 62% completion in the concurrent arm and 73% in the sequential arm. These results are relatively similar to those reported in other cervical cancer trials, and highlight the importance of improving toxicity management in clinical practice and future studies.…”
Section: Commentarymentioning
confidence: 97%
See 1 more Smart Citation
“…Treatment discontinuation rates were high in the chemotherapy arms, 5 with 62% completion in the concurrent arm and 73% in the sequential arm. These results are relatively similar to those reported in other cervical cancer trials, and highlight the importance of improving toxicity management in clinical practice and future studies.…”
Section: Commentarymentioning
confidence: 97%
“…The trial recruited across eight centers in China between 2008 and 2015 and included patients with FIGO stage IB1-IIA2 squamous cell, adenosquamous carcinoma, and adenocarcinoma of the cervix, and at least one risk factor following radical hysterectomy including lymph node metastasis, positive parametrium or margin, lymphovascular space involvement, or deep stromal invasion. 5 One thousand and fortyeight women were randomized to adjuvant radiation (radiation arm), concurrent chemo-radiation with weekly cisplatin (concurrent arm), or sequential treatment with 3 weekly cisplatin and paclitaxel, administered two cycles before and two after radiotherapy (sequential arm). The majority of enrolled patients had squamous cell histology (>85%) and tumor size was ≤4 cm in approximately 75% of women.…”
Section: Commentarymentioning
confidence: 99%
“…A phase III trial comparing sequential chemoradiation vs. radiation alone or concurrent chemoradiation in adjuvant treatment after radical hysterectomy for stage IB1–IIA2 cervical cancer (STARS study, NCT00806117) has been reported in ASCO annual meeting [ 8 9 ]. In the intention-to-treat population, sequential chemoradiation was associated with a higher 3-year disease-free survival than radiation alone (90% vs. 82%; hazard ratio [HR]=0.52; 95% confidence interval [CI]=0.35–0.76) and concurrent chemoradiation (90% vs. 85%; HR=0.65; 95% CI=0.44–0.96).…”
Section: Uterine Cervixmentioning
confidence: 99%
“…A recently concluded phase III randomized controlled trial (RCT) showed sequential chemoradiation (paclitaxel-cisplatin followed by radiotherapy, again followed by paclitaxel-cisplatin) after surgery resulted in improved disease-free survival (DFS) and lowered the risk of death from cervical cancer in patients with adverse pathological factors 19 . In this study, 1048 patients were equally randomized across three arms to receive either adjuvant RT, CCRT or sequential chemotherapy followed by RT after radical surgery 19 . Data showed that DFS and OS were significantly improved in the sequential arm as compared to RT alone [three-year DFS rate, 90 vs .…”
Section: Systemic Therapy As Concurrent Treatmentmentioning
confidence: 99%
“…82%; hazard ratio (HR) 0.52; 95% confidence interval (CI), 0.35-0.76 and five-year risk of death, 92 vs . 88%; HR, 0.58; 95% CI, 0.35-0.95] 19 . There was improved DFS for sequential arm as compared to concurrent arm (90 vs. 85%; HR 0.65; 95% CI, 0.44-0.96) 19 ; however, there was no difference between the CCRT versus RT alone arms 19 and requires confirmation in future trials.…”
Section: Systemic Therapy As Concurrent Treatmentmentioning
confidence: 99%